Public sector procurement of medicines in the Philippines - Michael Ralph M. Abrigo; Gina A. Opiniano; Zhandra C. Tam; Sherryl A. Yee; Katha Ma-i M. Estopace (Philippine Institute for Development Studies (PIDS), 2021)
The Philippine government plays an increasingly significant role in the provision of drugs and medicines. Over the last half decade, direct public procurement more than doubled from PHP 7.8 billion in 2014 to PHP 20.1 billion in 2019. In this study, we document government procurement practices as applied to drugs and medicines, with emphasis on instituted information revelation mechanisms to promote transparency. Among the almost 50,000 records in 2019 that we analyzed, we find that about a third of posted procurement opportunities for drugs and medicines had insufficient descriptions available to allow purchase. Further, we find that mandated price caps are associated with longer posting period and greater propensity for failed procurement, but not necessarily with cheaper procurement prices.
Keywords: 330; Public procurement; Drugs and medicines; Drug Price Reference Index; Philippine Government Electronic Procurement System